Employment Situation of Micro Enterprises in Papum Pare District of Arunachal Pradesh (International Journal of Food and Nutritional Sciences, 2022)
The number of employment generation, resource utilization, developing infrastructure, promoting higher standard of living, bringing equality in rich and poor people, eradicating the poverty, educating the people, increasing the per capita income, educating for better life, educating for self-dependency, spreading rationality, awareness among the public, allowing to participate in economic growth of the nation etc. are some of the important socio-economic impact of MSMEs, irrespective of how long and difficult process is to set up an MSMEs and running it successfully. The purpose of the present study is to bring in light the Micro enterprises and its employment generating efficiency in Papum Pare district of Arunachal Pradesh. The paper has been designed in such a way that it shows the employment status of Micro enterprises in Papum Pare district. The size, category, education level, remuneration, etc. of the workers/employees are taken as key elements for the study. The study is based on both primary as well as secondary data, which has been analyzed with statistical tool for better understanding.